Evolution of Orbital Parameters of Space Debris considering Orbital Maneuvers and Ground-Based Laser - Formiga, Jorge K.-S. [UNESP]; Santos, Denilson P.-S. [UNESP]; Moraes, Rodolpho V. [UNESP]; Prado, Antonio F.-B.-A. (Curran Associates, 2024)
Space debris events are becoming increasingly common in regions where they reach a critical density, resulting in a heightened risk of collisions. Ground-based lasers, when precisely directed, can induce a propulsive effect that alters the perigee of particles, leading to their rapid incineration upon re-entry into Earth's atmosphere or facilitating orbital adjustments. Our objective was to assess the efficacy of such orbital maneuvers, accounting for both gravitational effects and the use of ground-based laser, as space debris—ranging from 1 cm to 10 cm in size and orbiting at altitudes between 100 and 1000 km—approaches Earth within a hypothetical heliocentric orbit. We conducted analyses by examining variations in orbital elements and energy following close approaches, employing single-pulse laser propulsion. Our analytical model considers factors such as laser fluence, debris attitude, and the relative motion between the laser and debris. Results indicate that the laser induces minor changes in ΔV, with a maximum energy efficiency, which can be accumulated to enhance re-entry energy. Consequently, it is possible to obtain a 30% increase in the variation of the orbital elements after the maneuver. Consequently, this study contributes a comprehensive examination of such maneuvers to the literature, highlighting their advantages over traditional orbital adjustments and delineating optimal conditions for collision avoidance and space debris mitigation. Enhancing the dynamic modelling and validating experimental outcomes is recommended to refine the understanding of these studies.
Keywords: Astrodynamics; Ground-based laser; Orbital elements; Orbital maneuvers; Space Debris